Perancangan Sistem Informasi Mutasi Siswa SMA pada Dinas Pendidikan Provinsi Jawa Barat - Meliyana Dwi Cahya; Leonardi Paris Hasugian (PETIR, 2019)
The West Java Provincial Office is a company engaged in education services, which has several parts, one of which is the High School Development (PSMA) field. PSMA itself has not used an information system in the registration process of student mutations, where problems faced by registrants want to request a mutation referral letter, referral letters are not always completed on time. registrars do not know the flow of procedures, and other constraints are on file storage that tends to accumulate. The purpose of the study is to notify the registrant that a referral letter has been completed, notify the registrant of the path - what paths must be done by the registrant and make it easier when searching the file for the registration mutation. The method used, namely using descriptive methods. which is aimed at gathering information about a problem. The results of this study are to notify the registrant that the referral letter has been completed or processed, notify the registrant of the path - what paths the registrant must do, and make it easier when searching the file for the registration mutation.